New virus 'not as dangerous' as the Nipah - Chua, Eddie (2003)
Head's of Universiti Malaya's Department of Medical Microbiology Prof Datuk Dr Lam Sai Kit, who discovered the Nipah virus, said the mortality rate for the new virus is 3.5 per cent compared with 11 times more for the Nipah virus.